Waterborne functional paints to control biodeteration - Bellotti, Natalia (2020)
Coatings are generally defined as any material (usually liquid) that may be applied as a thin continuous layer to a surface. Paint is a term traditionally used to describe a specific dispersion system constituted by pigments, binder(s) (polymer or resin), solvents, and additives. These pigmented systems are designed for application to a substrate as a thin layer which is converted to an opaque solid film after application unlike of lacquers or varnishes. Therefore, paint is any pigmented coating. Coatings are usually applied as multilayered systems, each layer performing a specific function. Mostly these systems are used for decorative and protective purposes, but depending on the surface to cover and the environmental conditions in service, additional properties are required. Examples of these films with additional functionalities, known as functional coatings, are self-cleaning, easy-to-clean (antigraffiti), self-healing, anticorrosive, hygienic, and antifouling.